Analysis Of Ichthyofauna Of Situ Bagendit and Water Quality Post-Revitalization: Water quality data, Fish Diversity and Abundance Data - Sidik, Abdul Faqih Fajar Sidik; Surtikanti, Hertien Koosbandiah; Hernawati, Hernawati; Haryono, Haryono (Bioeksperimen: Jurnal Penelitian Biologi, 2025)
Situ Bagendit is one of the natural lakes in Garut Regency that has experienced a decline in environmental quality, so revitalization was carried out to improve the ecosystem and increase tourist attractions. Sampling at three observation stations based on water characteristics. The parameters observed include biotic factors (fish diversity) and abiotic factors (physical and chemical parameters of water. The Shannon-Wiener diversity index is used to assess the stability of the fish community, while water quality is analyzed based on water quality standards according to PP No. 22 of 2021 and lake trophic classification. The results of the study showed that water quality data that did not meet the threshold according to PP No. 21 of 2021 were water clarity (75-136 cm), chemical oxygen demand (COD) (21-31 mg/L), total nitrogen (1.22-1.59) and conductivity (506-588 μs/cm). Fish diversity is at a moderate level with an index of 1.22. The abundance value ranges from 4-55% with the highest abundance value being the hemichromis elongatus species (zebra tilapia), but there is no dominant species. A fish species found as an indicator of pollution is the janitor fish (pterygoplichthys pardalis) due to its high adaptability to polluted water. While several water quality parameters have not fully met class II quality standards, especially in terms of brightness, COD, total nitrogen, and conductivity. Ecosystem conditions of Situ Bagendit still requires sustainable management to maintain water quality and biodiversity.